Evaluation of Sperm and Morphometric Parameters of Testicular Tissue Following Curcumin Administration in Rats After Varicocele Induction - Mohammadreza Sadraie (Qom University of Medical Sciences, 2021)
Background and Objectives: Varicocele is the abnormal dilation and twisting of the veins of the pampiniform network, the spermatic cord of the testis. This event is associated with increased oxidative stress and decreased antioxidant capacity. The consequence of varicocele is a reduction in the quality of sperm parameters and defects in spermatogenesis. Curcumin has been introduced as an antioxidant with multiple and modulating potentials in biological activities. This study investigates the effect of curcumin on sperm parameters and the histological status of testicular tissue in rats with varicocele. Methods: For this study, 50 male Wistar rats were examined in 5 different groups: control, sham, varicocele, varicocele treated with curcumin 50 mg/kg, and varicocele treated with curcumin 100 mg/kg. Varicocele was induced through partial occlusion of the left renal vein. Then, sperm parameters and histological status of testicular tissue were assessed and analyzed using ANOVA test after 2 months of curcumin administration in varicocele rats. Results: This study showed that varicocele led to a significant decrease in motility percentage (P= 0.007), sperm concentration (P= 0.036), and a significant increase in abnormal sperm morphology (P≥0.05) compared to the control group. Although administration of curcumin in varicocele rats with concentrations of 50 and 100 mg/kg led to an improvement in sperm parameters, only in varicocele rats received 100 mg/kg curcumin, the concentration (P= 0.032) and total sperm motility (P= 0.04) significantly improved compared to varicocele group. In addition, curcumin improved the tissue damage caused by varicocele and increased the spermatogenesis index. Conclusion: The present study showed that curcumin improves the low quality of sperm parameters and can be a treatment strategy for future male infertility.